1992
DOI: 10.1007/bf01703085
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determination and genetic content of an 8.9-kb restriction fragment in the short unique region and the internal inverted repeat of Marek's disease virus type 1 DNA

Abstract: The DNA sequence (8.9 kb) covering about 70% of the short unique region (Us) and part of the short inverted repeat of the Marek's disease virus type 1 GA strain was determined. Computer analysis of the sequence showed the presence of nine potential open reading frames (ORFs), consisting of more than 300 nucleotides in the Us region. Of these ORFs, four were found to be homologous to US10 (minor virion protein), US3 (protein kinase), US2, and US6 (gD) in the Us region of alpha-herpesvirus herpes simplex virus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…The US10 ORF probe hybridized to three transcripts of 2.5, 1.7, and 0.9 kb in RNA extracted from cells infected with CVI988. Consistent with our previous report (48), the probe did not detect any transcripts in cells infected with rMDV1-US10P(F), indicating that no US10 gene product is expressed in cells infected with the virus. The NDV-F cDNA probe hybridized to four transcripts of 4.2, 3.4, 2.6, and 2.1 kb in RNAs extracted from cells infected with rMDV1-US10P(F), but not from cells infected with CVI988.…”
Section: Analysis Of Transcripts From the Inserted Ndv-f Gene In Cellsupporting
confidence: 78%
“…The US10 ORF probe hybridized to three transcripts of 2.5, 1.7, and 0.9 kb in RNA extracted from cells infected with CVI988. Consistent with our previous report (48), the probe did not detect any transcripts in cells infected with rMDV1-US10P(F), indicating that no US10 gene product is expressed in cells infected with the virus. The NDV-F cDNA probe hybridized to four transcripts of 4.2, 3.4, 2.6, and 2.1 kb in RNAs extracted from cells infected with rMDV1-US10P(F), but not from cells infected with CVI988.…”
Section: Analysis Of Transcripts From the Inserted Ndv-f Gene In Cellsupporting
confidence: 78%
“…HVT and MDV have genome structures similar to those ofalphaherpesviruses (Cebrian et al, 1982;Fukuchi et al, 1984;Igarashi et al, 1987) and have numerous genes that are homologous to and collinear with those of varicella-zoster virus and herpes simplex virus (HSV) (Buckmaster et al, 1988). Sequencing studies Sakaguchi et al, 1992) have indicated that MDV U s encodes proteins homologous to HSV US1, US2, protein kinase (PK), US10 and glycoproteins gD, gI and gE but that three proteins (SORF1, SORF2 and SORF3) have no counterparts in HSV or any other mammalian herpesvirus. Using rabbit antisera directed against fusion proteins expressed in Eseheriehia coli, characterized MDV USI, US10, US2, PK and glycoproteins gI and gE in extracts of infected duck embryo fibroblasts (DEF) by radioimmunoprecipitation assay (RIPA) but were unable to identify MDV gD.…”
Section: Herpesvirus Of Turkeys (Hvt) Is Classified As Meleagrid Herpmentioning
confidence: 99%
“…sequenced a 5-5kbp EcoRI fragment mapping in the short unique segment (Us) of MDV and identified herpes simplex virus type 1 (HSV-1) homotogues of US2, protein kinase (PK), glycoprotein D (gD) and glycoprotein I (gI), and one short open reading frame (ORF4) which showed some similarity to HSV-1 glycoprotein G (gG). More recently, Brunovskis & Velicer (1992), Velicer et al (1992) and Sakaguchi et al (1992) reported the nucleotide sequence of MDV U s and characterized a number of Us-encoded polypeptides. The 11 160 bp long MDV U s DNA was found to contain at least 11 ORFs; seven of these were found to be exclusively homologous to alphaherpesvirus U s genes [US1, US10, US2, PK (US3), gD, gI and glycoprotein E (gE) homologues of HSV-1], one ORF was reported to be homologous to fowlpox virus ORF4 described by Tomley et al (1988), and three ORFs had no apparent 0001-1608 © 1993 SGM relationship to any sequences in protein databases and were considered to be MDV-specific.…”
Section: Introductionmentioning
confidence: 99%